3D model for CAR‐mediated cytotoxicity using patient‐derived colorectal cancer organoids. (29th April 2019) - Schnalzger, Theresa E; de Groot, Marnix HP; Zhang, Congcong; Mosa, Mohammed H; Michels, Birgitta E; Röder, Jasmin; Darvishi, Tahmineh; Wels, Winfried S; Farin, Henner F
Abstract: Immunotherapy using chimeric antigen receptor (CAR)‐engineered lymphocytes has shown impressive results in leukemia. However, for solid tumors such as colorectal cancer (CRC), new preclinical models are needed that allow to test CAR‐mediated cytotoxicity in a tissue‐like environment. Here, we developed a platform to study CAR cell cytotoxicity against 3‐dimensional (3D) patient‐derived colon organoids. Luciferase‐based measurement served as a quantitative read‐out for target cell viability. Additionally, we set up a confocal live imaging protocol to monitor effector cell recruitment and cytolytic activity at a single organoid level. As proof of principle, we demonstrated efficient targeting in diverse organoid models using CAR‐engineered NK‐92 cells directed toward a ubiquitous epithelial antigen (EPCAM). Tumor antigen‐specific cytotoxicity was studied with CAR‐NK‐92 cells targeting organoids expressing EGFRvIII, a neoantigen found in several cancers. Finally, we tested a novel CAR strategy targeting FRIZZLED receptors that show increased expression in a subgroup of CRC tumors. Here, comparative killing assays with normal organoids failed to show tumor‐specific activity. Taken together, we report a sensitive in vitro platform to evaluate CAR efficacy and tumor specificity in a personalized manner. Synopsis: Establishment of a preclinical in vitro organoid model allows testing the efficacy and safety of solid tumor cancer immunotherapy with chimeric antigen receptor (CAR)‐engineered lymphocytes in a tissue‐like environment. 3D live‐imaging of single colorectal cancer (CRC) organoids is highly sensitive and allows to validate treatment assumptions to minimize therapy side effects. Co‐culture of human natural killer (NK) cells with normal or CRC organoids on an ECM layer allows stable effector‐target cell interaction. Luciferase‐based cytotoxicity assessment is benchmarked with EPCAM‐directed effector NK cells. Low expression of EGFRvIII neoantigen is sufficient to render CRC organoids susceptible to lysis. CAR targeting of FRIZZLED receptors in intestinal organoids reveals off‐target cytotoxicity against wild‐type epithelia of human origin. Abstract : A preclinical organoid co‐culture allows testing of immunotherapy with chimeric antigen receptor (CAR)‐engineered lymphocytes in a personalised tissue‐like environment.